Physical science: With environment and other practical applications - Turk, Jonathan (Saunders College, 1986)
This book is an introduction to the elements of physics, chemistry, geology, meteorology, and astronomy for the non- science major. The requirement for a foundation in basics imposes some necessary sequences. Motion is discussed with introducing Newtons's Laws, chemistry necessarily depends on an understanding of atomic structure, and any section of geology must include a discussion of plate tectonics. Environmental issues also help to illustrate the principles and to enliven the reading. In addition to the features mentioned above, the following study aids are provided: * Chapter summaries. Each chapter is concluded with a short summary that serves as an aid for easy review of the text. The summary is supplemented with a checklist of key words. * Glossary. An extensive glossary of terms used in the text is provided at the end of the book. * Appendix. The appendix explains significant figures and proportionality. The appendix also includes conversion formulas for temperature scales, a simple derivation of the kinetic energy equation, a slightly more mathematical treatment of the decibel scale, and tables of conversion factors and atomic weights. * Intructor's guide. An intructor's guide is also available. It includes answers to the questions at the end of each chapter, and two sample multiple choice tests for each chapter